Isolasi dan Karakterisasi secara Morfologi dan Biokimia Khamir dari Limbah Kulit Nanas Madu (Ananas comosus L.) untuk Produksi Bioetanol - Akbar, Galih Pertiwi; Kusdiyantini, Endang .; Wijanarka, W . (Berkala Bioteknologi, 2019)
Yeast is a group of microorganisms that are easily found in fermented products, soil, water, plant tissues, leaves, flowers and fruits. Bioethanol is one of the alternative energy produced by yeast through fermentation. This study aims to isolate and characterize yeast morphologically and biochemically yeast from honey pineapple skin waste for bioethanol production. Isolation was carried out using PDAY + chloramphenicol media. Morphological characterization were carried out by observing colony morphology, cell and yeast asexual reproduction. Biochemical characterization included carbon and nitrogen assimilation, urea hydrolysis test, protein hydrolysis test, glucose acid production test, high glucose tolerance test, ethanol tolerance test and production and analysis of fermented bioethanol levels by yeast isolates. From the isolation process found 6 yeast isolates, where isolates Ep-1 and Ep-2 are similar to Wickerhamia sp., Ep-3 and Ed-3 similar to Zygosaccharomyces sp. and isolates Ed-1 and Ed-2 are similar to Saccharomyces sp.Characteristics possessed by yeast isolates showed the ability to assimilate several sources of carbon and ammonium sulfate; able to hydrolyze proteins; some are able to produce acid; cannot hydrolyze urea; tolerant to glucose concentrations of 40%, 50% and 60%; tolerant to ethanol 5%, 10% and 15%; and able to produce bioethanol.Ep-1 isolates are known to have the most potential for ethanol production because they are tolerant to 60% glucose concentration and 15% ethanol and the level of bioethanol produced is 12.00%. Key words : yeast, honey pineapple skin waste, characterization, bioethanol